2020
DOI: 10.1186/s13673-020-00223-z
|View full text |Cite
|
Sign up to set email alerts
|

Transient ischemic attack analysis through non-contact approaches

Abstract: IntroductionTransient ischemic attack (TIA) is a transient neurological disorder caused by focal ischemia of the brain or retina without acute infarction. The clinical symptoms usually last less than 1 hour and the neurological function can return to normal after the onset [1]. TIA is characterized by sudden onset, short duration and high frequency of attack. Currently, the causes of TIA are generally recognized by the medical community as follows :(1) Embolus in arterial blood flows into the brain, resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…suggested that their study was potential. In 2020, Zhang, et al [112] proposed a contactless approach to detect TIA in the indoor environment. They employed a microwave sensing platform to collect monitoring data and then performed the support vector machine (SVM) and the random forest (RF) to build the recognition model.…”
Section: Transient Ischemic Attackmentioning
confidence: 99%
“…suggested that their study was potential. In 2020, Zhang, et al [112] proposed a contactless approach to detect TIA in the indoor environment. They employed a microwave sensing platform to collect monitoring data and then performed the support vector machine (SVM) and the random forest (RF) to build the recognition model.…”
Section: Transient Ischemic Attackmentioning
confidence: 99%
“…It is concluded that the prediction of ANN model is better than that of linear regression model. In order to monitor transient Islamic attack in the interior environment and improve risk management of stroke, two machine learning algorithms support vector machine (SVM) and random forest (RF) are used to establish prediction models respectively [ 37 ]. The accuracy rate has reached more than 97%.…”
Section: Basic Theory Of Sinter Blending Model Algorithmsmentioning
confidence: 99%